Blockade of CTLA-4 and Tim-3 pathways induces fetal loss with altered cytokine profiles by decidual CD4(+)T cells - Wang, Songcun (Cell Death Dis, 2019)
The single and/or combination use of immune checkpoint blockade therapies in human infectious diseases and cancer are rapidly expanding. Despite early efforts, substantial uncertainty remains about the safety and efficacy of immune checkpoint blockade in some populations. Cytotoxic T-lymphocyte-associated protein 4 (CTLA-4) and T-cell immunoglobulin mucin-3 (Tim-3) are the major targetable co-inhibitory receptors on T cells. Here we showed that in animal studies, treatment with either CTLA-4- or Tim-3-blocking antibody caused greater susceptibility to fetal loss with altered cytokine profiles by decidual CD4(+)T (dCD4(+)T) cells. CTLA-4 and Tim-3 pathways appeared to play key roles in maintaining maternal-fetal tolerance by regulating the function of dCD4(+)T cells. In addition, the abnormality in number and functionality of dCTLA-4(+)Tim-3(+)CD4(+)T cells was associated with miscarriage. These findings underscored the important roles of the CTLA-4 and Tim-3 pathways in regulating dCD4(+)T cells function and maintaining normal pregnancy. Our study also emphasized the importance of careful consideration of reproductive safety when choosing immune checkpoint blockade therapies in real world clinical care.